2001
DOI: 10.1021/jf010592k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Operating Parameters on the Use of the Microwave-Assisted Process (MAP) for the Extraction of Azadirachtin-Related Limonoids from Neem (Azadirachta indica) under Atmospheric Pressure Conditions

Abstract: The use of the microwave-assisted process (MAP) for the extraction of azadirachtin-related limonoids (AZRL) from various parts of the neem tree was investigated under different operating conditions. The influence of microwave power, solvent, and irradiation time on the recovery of AZRL was studied. The efficiency of the microwave-assisted extraction (MAE) of the seed kernel, the seed shell, the leaf, and the leaf stem was compared to that of conventional extraction methods. The content of AZRL in the extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…It has been demonstrated that microwave energy had the capacity of enhancing the extraction yields of the target compounds as opposed to conventional methods (Dai et al 1999(Dai et al , 2001Martino et al 2006;Nemes 2007;Williams et al 2004;Yang et al 2004). The enhancing effect of microwaves is due to the interactions between the electric component of the microwave field with the dipolar molecules and the ionic species present in the extraction mixtures (solvent/reagent+sample; Meda et al 2005;Orsat et al 2005;Raghavan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that microwave energy had the capacity of enhancing the extraction yields of the target compounds as opposed to conventional methods (Dai et al 1999(Dai et al , 2001Martino et al 2006;Nemes 2007;Williams et al 2004;Yang et al 2004). The enhancing effect of microwaves is due to the interactions between the electric component of the microwave field with the dipolar molecules and the ionic species present in the extraction mixtures (solvent/reagent+sample; Meda et al 2005;Orsat et al 2005;Raghavan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted extraction (MAE) is another way of accelerating the extraction of compounds from plant materials. MAE showed high efficiency in extracting essential oils [28][29][30], camptothecin alkaloids [31], and limonoids in neem trees [32]. MAE was also effective in extracting the phytochemicals in peanut [33].…”
Section: Preparation Of Botanical Samples For Initial Screening Testsmentioning
confidence: 96%
“…Microwave-assisted extraction (MAE) uses microwave energy and solvents to extract target compounds from solid and semisolid samples. The highly localized temperature and pressure can cause selective migration of target compounds from the material to the surroundings at a more rapid rate and with equivalent or even higher extraction yield compared with conventional extraction [11]. With the big advantages of reducing both the extraction time and solvent consumption, this simple and consistent technique has been widely applied.…”
Section: Introductionmentioning
confidence: 99%